UPAYA PENEGAKAN HUKUM TERHADAP PELAKU TAWURAN ANTAR PELAJAR - Irma Yuliani; Misdayanti Harina Simatupang (Al Qadhi, 2023)
Fighting between students is a serious problem that threatens safety and the educational environment. This research examines the various efforts of law enforcement officials in overcoming brawls between students. This research uses a qualitative approach, by collecting data from various sources including legal literature, related studies and regulations related to violence in educational institutions. The results show that the legal protection of student struggles includes important steps. Firstly, a clear definition of fighting as physical violence between students is key to establishing a legal basis. The involvement of law enforcement officials such as the police and related agencies is crucial in the investigation, arrest, prosecution, and trial of those involved in this struggle. In addition to law enforcement, prevention is also a key focus. Schools participate in implementing prevention programmes, including conflict resolution training and creating a safe learning environment. The role of families in monitoring children's behaviour and supporting preventive activities is also a key factor in resolving disputes between students.